Non-Hematopoietic MLKL Protects Against Salmonella Mucosal Infection by Enhancing Inflammasome Activation - Yu, Shui-Xing; Chen, Wei; Liu, Zhen-Zhen; Zhou, Feng-Hua; Yan, Shi-Qing; Hu, Gui-Qiu; Qin, Xiao-Xia; Zhang, Jie; Ma, Ke; Du, Chong-Tao; Gu, Jing-Min; Deng, Xu-Ming; et al. (Frontiers in Immunology, 2018)
The intestinal mucosal barrier is critical for host defense against pathogens infection. Here, we demonstrate that the mixed lineage kinase-like protein (MLKL), a necroptosis effector, promotes intestinal epithelial barrier function by enhancing inflammasome activation. MLKL-/- mice were more susceptible to Salmonella infection compared with wild-type counterparts, with higher mortality rates, increased body weight loss, exacerbated intestinal inflammation, more bacterial colonization and severe epithelial barrier disruption. MLKL deficiency promoted early epithelial colonization of Salmonella prior to developing apparent intestinal pathology. Active MLKL was predominantly expressed in crypt epithelial cells, and experiments using bone marrow chimeras found that the protective effects of MLKL were dependent on its expression in non-hematopoietic cells. Intestinal mucosa of MLKL-/- mice had impaired caspase-1 and GSDMD cleavages and decreased IL-18 release. Moreover, administration of exogenous recombinant IL-18 rescued the phenotype of increased bacterial colonization in MLKL-/- mice. Thus, our results uncover the role of MLKL in enhancing inflammasome activation in intestinal epithelial cells to inhibit early bacterial colonization.